I am not a public figure, I am a public servant: How public servants experience harsh discourse and harassment and their proposals for solutions - Bjarnadóttir, Þóra; Ólafsson, Jón Gunnar (Stofnun stjórnmála og stjórnsýslu, 2024)
The purpose of this study is to explore how public servants in Iceland experience harsh discourse and harassment in their profession, and to investigate resources to combat this type of behavior. Increasingly ruthless discourse, commonly blamed on social media, has led to harsher communication and harassment against public servants. A qualitative study was conducted in which public servants in Iceland were interviewed. The approaches of grounded theory and thematic analysis were used to extract themes from the data. The results of the study are divided into five themes: Altered discourse concerning the government, public servants’ personal experience regarding harsh discourse and harassment, fear and defense mechanisms of public servants surrounding future threats, the powerless public servant, and helpless public servants who lack resources when faced with harsh discourse or harassment. Interviewees agreed that the public discourse in Iceland lacked boundaries towards public servants. They felt defenselessness against public discussion because they were obliged to observe secrecy and could not rectify misinformation on social media or in the media. Several had experienced severe cases of harsh discourse and harassment, for example name and photo disclosures, doxing, ambushing, stalking, threats, cyberbullying and physical violence. They perceived the system as useless and felt that they did not receive appropriate assistance. Interviewees were asked to propose solutions to the problem, which included better support for victims, a joint contingency plan for the government, strengthening legal measures to protect public servants, and the hiring of press secretaries for government offices. Markmið rannsóknarinnar er að kanna upplifun opinberra starfsmanna á Íslandi af óvæginni umræðu og áreitni í starfi, ásamt því að skoða hvað sé til ráða til að bregðast við slíkri háttsemi. Breytt og harkalegri samfélagsumræða, meðal annars fyrir tilstilli samfélagsmiðla, hefur leitt til aukinnar óvæginnar umræðu og áreitni í ...